Problems in Reading Comprehension of TOEFL Prediction Test - Yuliana Friska (Journal of English Language and Education, 2022)
TOEFL is a standardized test that has been used as requirement to graduate from university. However, students frequently struggle to pass the TOEFL reading test. Therefore, this study was aimed to identify (1) which sub-skills were the most challenging for students in reading comprehension of TOEFL test and (2) factors affecting the students’ difficulty in answering the reading comprehension section of the TOEFL test. This study applied both quantitative and qualitative approaches. A total of 32 students from various majors of Universitas Pamulang were samples for the test. The data were obtained by test results and interview results. The test result showed that the most challenging problems in reading comprehension were vocabulary (25 %), unstated detail question (20%), stated detail question (18%), pronoun referent question (15%), inference question (12%), and main idea question (10%). Moreover, the interview results revealed that lack of vocabulary, slow reading, and lack of strategy were factors affecting students’ difficulty. Therefore, TOEFL teachers and trainers are strongly advised to devote more time to prepare for the topics with the highest percentage of errors.